The best position of bone grafts in the medial open-wedge high tibial osteotomy: A finite element analysis. (January 2023) - Pan, Chen-shuai; Wang, Xiao; Ding, Ling-zhi; Zhu, Xian-ping; Xu, Wei-fang; Huang, Li-xin
Highlights: Medial open-wedge high tibial osteotomy is becoming more widely used in patients with medial knee osteoarthritis. Structural graft filling in the osteotomy area can increase bone healing, providing conditions for early full weight-bearing. The posterior part of the osteotomy area is the best position for bone graft placement. Stress of posterior bone grafts mainly concentrated at the edge. Abstract: Background and objective: The application of wedge-shaped bone grafts can increase the biomechanical stability of knee during the medial open-wedge high tibial osteotomy (MOWHTO) by reducing the von Mises stress of the medial plate and lateral cortical hinge area. However, the optimal position of bone grafts it remains unclear, so we aimed to determine search for the optimal position of the bone grafts in MOWHTO by using finite element analysis. Methods: In the finite element analysis, MOWHTO models were established with three different osteotomy distraction heights and assembled into four groups according to different conditions, including the no bone grafts (NBG) group, the anterior bone grafts (ABG) group, the middle bone grafts (MBG) group, and the posterior bone grafts (PBG) group. Based on previous studies, 600 N and 1800 N loads were applied to the knee joint to simulate the static forces during a double and single leg stance to measure the von Mises stress of the medial implant area and lateral hinge area, the maximum displacement of different models, the relative displacement of the osteotomy area and the stress distribution in the bone grafts. Results: Compared to the NBG and ABG groups, the stress of the lateral cortical hinge area and the medial implate area was significantly lower in the PBG group. For example, under the 600N force load, when the height of the osteotomy area was 10 mm, 15 mm, and 20 mm, the maximum von Mises stress of the medial implate area and lateral cortical hinge area in the NBG group were 140, 141, 172, and 53, 57, 60 MPa, respectively. Compared with the NBG group, the maximum von Mises stress of the medial implate area and lateral cortical hinge area in the PBG group were reduced by 45%, 56%, 63% and 14%, 39%, 68% at distraction height of 10 mm, 15 mm, and 20 mm, respectively. The bone grafts in the posterior parts provide the best stability, with the stress of the middle and posterior bone grafts are mainly concentrated in the edge. Conclusions: The posterior part of the osteotomy area is the best position for bone graft placement since it provides optimal stability and reduces von Mises stress in the medial plate and lateral cortex hinge area, with the stress of the posterior bone grafts mainly concentrated in the edge. These findings guide bone graft placement sites in clinical surgery and are a basis for future research on bone graft materials and structures in MOWHTO.